2009
DOI: 10.1103/physreve.79.011904
|View full text |Cite
|
Sign up to set email alerts
|

Noise-assisted spike propagation in myelinated neurons

Abstract: We consider noise-assisted spike propagation in myelinated axons within a multi-compartment stochastic Hodgkin-Huxley model. The noise originates from a finite number of ion channels in each node of Ranvier. For the subthreshold internodal electric coupling, we show that (i) intrinsic noise removes the sharply defined threshold for spike propagation from node to node, and (ii) there exists an optimum number of ion channels which allows for the most efficient signal propagation and it corresponds to the actual … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0
23

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 31 publications
5
41
0
23
Order By: Relevance
“…the so-called channel noise which is inherently coupled to the electrical properties of the axonal cell membrane [19][20][21]. Interestingly, it has been shown that intrinsic channel noise does not only lead to the generation of spontaneous action potentials [22], but as well affects the neuronal dynamics at different levels, namely: (i) it can boost the signal quality [14,15], (ii) enhance the signal transmission reliability [23], (iii) cause frequency-and phase-synchronization features [24][25][26][27][28] and (iv) may result in a frequency stabilization [29], to name but a few.…”
Section: Introductionmentioning
confidence: 99%
“…the so-called channel noise which is inherently coupled to the electrical properties of the axonal cell membrane [19][20][21]. Interestingly, it has been shown that intrinsic channel noise does not only lead to the generation of spontaneous action potentials [22], but as well affects the neuronal dynamics at different levels, namely: (i) it can boost the signal quality [14,15], (ii) enhance the signal transmission reliability [23], (iii) cause frequency-and phase-synchronization features [24][25][26][27][28] and (iv) may result in a frequency stabilization [29], to name but a few.…”
Section: Introductionmentioning
confidence: 99%
“…With this work, we extend our prior study [15] on the effect of channel noise on the propagation of action potentials along myelinated axons. In terms of transmission reliability we are discussing the influence of the coupling strength between neighboring nodes of Ranvier and that of strong intrinsic noise.…”
Section: Introductionmentioning
confidence: 74%
“…In order to model the signal transmission along myelinated axons, we consider a compartmental stochastic HodgkinHuxley model [15]. Accordingly, each node of Ranvier is modeled by a stochastic generalization of the Hodgkin-Huxley model, which extends the applicability of the original Hodgkin-Huxley model [2] towards stochastic dynamics of the membrane potential of finite-size ion channel clusters [3,18].…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations